A global potential energy surface and dynamics study of the Au+ + H2 → H + Au+H reaction. Issue 57 (17th July 2017) - Wang, Shufen; He, Di; Li, Wentao; Chen, Maodu
Abstract : A global potential energy surface (PES) of the ground state of the Au + H2 system was constructed using a neural network method with permutation invariant polynomials. Abstract : A global potential energy surface (PES) of the ground state of the Au + H2 system was constructed using a neural network method with permutation invariant polynomials. More than 40 000 ab initio points were calculated using a multi-reference configuration interaction approach, and these were adopted into a fitting process; the root mean square error was 0.02 eV. The topography of the present PES was compared in detail with the PES reported by Dorta-Urra ( J. Chem. Phys., 135, 2011, 091102). The potential well in the present PES is about 0.12 eV deeper than the previous PES. The dynamics calculations based on these two PESs were performed by the time-dependent quantum wave packet method with a second-order split operator. The reaction probability, integral cross section and differential cross section based on these two PESs were calculated in this work. The results obtained from these two PESs were compared with the experimental data. It was clear that the integral cross section calculated by using the present PES is closer to the experimental data than the one obtained from Dorta-Urra PES. In addition, the reaction mechanism of the title reaction changed from an indirect reaction to an abstraction reaction as the collision energy increased.